IMPACT OF INTENSIFIER AS WOMEN’S PERSUASION STRATEGY IN POLITICS - Britney Caren Joseph; Widyastuti Soewito (Universitas Sebelas Maret, 2023)
This study analyses impact of intensifers as persuasive language strategy in politics used by female politician in the presidential debate. The data were in the form of words and sentences. Two primary sources are used in data gathering: vice-presidential debate transcription from USA Today and CNN. The study is a qualitative method focusing to construe in-depth analysis. The theoretical framework used as the main theory to analyse the data were Lakoff’s (1975) women language feature and Quirk et al. (1992) types of intensifier. Two research questions are formulated: 1) What type of intensifiers were used by the female politicians in the debate? 2) What is the function of intensifiers used by the female politicians in the debate? The result found that the three types of intensifiers were found. First, the emphasizers were found to be frequently used when female politicians aimed to highlight an important statement. The adding of the emphasis operates as a device to enhance the urgency and seriousness of a particular issue. Second, the amplifiers were found to be frequently used when female politicians wanted to amplify certain statement. Amplifier is a rhetorical and stylistic device that means to make something stronger, louder, and more intense. Finally, downtoners were found to be frequently use when female politicans wanted to reduce the intensity or lessen the force of a particular statement. Furthermore, it was discovered that the two female politicians were using these words as part of a persuasive strategy to convince the constituent.